Perebutan Kekuasaan Internal NU - Muslimin, Imam (UIN Maulana Malik Ibrahim Malang, 2004)
Since its establishment, NU has always been characterized by various internal rivalries between fractions fighting for influence. This paper discusses the internal upheaval of NU. Furthermore, the paradigmatic camps, ideological camps and competing fractions are also reviewed comprehensively. The result of competition for the power, most obviously, is the shift in power-sharing internally. At the time of its establishment until the 1950s, the greatest part of power in NU was held by non-politician kiai (syuriah) fraction, then the politician fraction (tanfidiyah) dominated it until the first half of the 1980s, and after that NU was in the hands of the fractions